Исследование особенностей факторов, влияющих на продолжительность цикла литья - Замета, Д. В. (ХНУРЭ, 2012)
In this article the features of duration casting wares cycle were probed by the method of casting under constraint. Calculation correlations for determination of duration casting cycle are offered
Keywords: цикл литья